2021
DOI: 10.2147/opth.s299655
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Cross-Sectional Imaging Features of IgG4-Related Orbitopathy in Comparison to Ocular Adnexal Lymphoma

Abstract: Aim To detect radiological features that, in addition to clinical findings, may aid in correct differentiation between IgG4-related ophthalmic disease (IgG4-ROD) and ocular adnexal lymphoma (OAL). Methods In this retrospective, single-center, comparative analysis, we compared cross-sectional imaging findings of 13 consecutive patients with histologically proven IgG4-ROD and a control group of 29 consecutive OAL-patients diagnosed between 10/2014 and 09/2019. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…44% of our patients presented with isolated lacrimal gland enlargement, which was comparable to 48% in the Japanese cohort reported by Sogabe et al 7 In contrast, EOM was reported as the most common site of involvement in 1 European cohort. 22 Forty-one of 115 (36%) of our patients had enlarged EOM, and only 9/41 (22%) of them suffered from diplopia, similar to previous reports. 7,23,24 IONE was associated with IgG4-ROD 9 and reactive lymphoid hyperplasia, 10 and it was found in 27% of our patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…44% of our patients presented with isolated lacrimal gland enlargement, which was comparable to 48% in the Japanese cohort reported by Sogabe et al 7 In contrast, EOM was reported as the most common site of involvement in 1 European cohort. 22 Forty-one of 115 (36%) of our patients had enlarged EOM, and only 9/41 (22%) of them suffered from diplopia, similar to previous reports. 7,23,24 IONE was associated with IgG4-ROD 9 and reactive lymphoid hyperplasia, 10 and it was found in 27% of our patients.…”
Section: Discussionsupporting
confidence: 90%
“…The lacrimal gland was the most frequently involved in 90% of our patients, similar to the Japanese,7,19 Korean,20 and American21 studies. 44% of our patients presented with isolated lacrimal gland enlargement, which was comparable to 48% in the Japanese cohort reported by Sogabe et al7 In contrast, EOM was reported as the most common site of involvement in 1 European cohort 22. Forty-one of 115 (36%) of our patients had enlarged EOM, and only 9/41 (22%) of them suffered from diplopia, similar to previous reports 7,23,24.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…41 However, another study in German patients did not find any CT imaging differences between both diseases. 42 An imaging finding highly suggestive of IgG4-ROD is the involvement of the trigeminal nerve branches, especially the infraorbital nerve (Fig. 3C), which has not been found in GO, orbital lymphoma, reactive lymphoid hyperplasia, idiopathic orbital inflammation, or adult xanthogranulomatous disease.…”
Section: Head and Neck Limited Phenotypementioning
confidence: 97%
“…Primary extraocular muscle lymphomas are rare, it accounts for about 0.1% and 8.7% of all extranodal lymphomas [24,25]. In most cases extraocular muscle involvement is due to infiltration of extramuscular masses [26,27].…”
Section: Alternative Causes Of Extraocular Muscle Enlargementmentioning
confidence: 99%